A critical overview of the current myofascial pain literature – July 2020. Issue 3 (July 2020) - Dommerholt, Jan; Hooks, Todd; Thorp, Jacob N.; Chou, Li-Wei
Abstract: We are sad to report that following this issue, Dr. Li-Wei Chou will no longer be able to contribute to this quarterly literature overview. Unfortunately, his work responsibilities have increased to such an extent that they need to take priority. On behalf of the team, we would like to thank Dr. Chou for his thoughtful and balanced reviews during the past few years. Not only were we able to include an occasional Chinese-language study, he also was able to assist us in interpreting more complex medical studies. Li-Wei, we wish you all the best professionally and personally, and of course, we cannot wait until our paths will cross again sometime in the future! You may have noted that this overview article was missing from the January 2020 issue of the journal due to an administrative mix up. With the current issue we aimed to catch up and therefore, you will find a greater number of reviewed articles than usual. It becomes increasingly challenging to cover the wide range of the published myofascial pain and trigger point (TrP) literature just due to its volume. In this edition, we included 10 basic research articles, 4 reviews, 14 articles on dry needling (DN), acupuncture, and injections, 3 on manual therapies, and 4 on other clinical approaches.